423. Molecular Epidemiology of ESBL E. coli Over a 2 Year Period in Worcester Massachusetts USA. (15th December 2022) - Hathaway, Nicholas J; Ward, Doyle V; Ellison, Richard T
Abstract: Background: Extended-spectrum beta-lactamase (ESBL) producing Escherichia coli are an increasing health burden contributing to a pandemic of resistant bacteria. Methods: To better understand the population genomics of ESBL E. coli, 129 phenotypically identified ESBL isolates collected between 2017-04 to 2018-11 from a single academic medical center underwent whole genome sequencing with the presence of antibiotic resistance genes identified by screening against the CARD database. The odds of phenotypic resistance to beta-lactam agents were calculated for each known resistance gene. A novel approach based on k-mer-enrichment among antibiotic resistance gene groups was developed to predict genes associated with phenotypic resistance. Results: Genomic analysis revealed that 60% of the ESBL isolates collected were pandemic strain ST131. All isolates contained at least 1 gene in the beta-lactamase family with a median of 3 different beta-lactamase genes being present. Ninety-five percent of isolates contained a CTX-M gene with 52% CTX-M-15, 43% CTX-M-27, 5% other CTX-M; 24% had OXA and 34% had TEM. The presence of CTX-M-15 significantly increased the odds of resistance to ampicillin-sulbactam (95% confidence interval 5.9-116.5, p-value < 1e-7), ceftazidime (4.2-25.9, p< 1e-6) and cefepime (3.6-20.1, p< 1e-5) but not to piperacillin-tazobactam (0.9-6.3, p 1). CTX-M-27 decreased the odds of resistance to these 4 beta-lactams (0.003-0.07, p< 1e-13; 0.04-0.3, p< 1e-05; 0.06-0.4, p< 0.001; 0.03-0.6, p 0.11). TEM-1 significantly increased the odds for ampicillin-sulbactam resistance (3.8-1036.7, p< 1e-3) but not for other beta-lactams. Our de novo sequence approach was able to identify the known genes listed above and also identified a 683 bp open reading frame with unknown function that had increased odds of resistance to piperacillin-tazobactam resistance (2.1-43.6, p< 1e-3). This 683 bp open reading frame did not share any homology with known beta-lactamases. Conclusion: The majority of phenotypic ESBL isolates contain multiple beta-lactamase genes. The presence of CTX-M-15 appears to increase the odds of resistance to key beta-lactam agents. Our novel k-mer-enrichment approach identified a novel marker of piperacillin-tazobactam resistance. Disclosures: All Authors : No reported disclosures.